2013
DOI: 10.21061/jte.v25i1.a.4
|View full text |Cite
|
Sign up to set email alerts
|

Developing Effective STEM Professional Development Programs

Abstract: Effective for Reviews during the 2015-2016 Accreditation Cycle Definitions While ABET recognizes and supports the prerogative of institutions to adopt and use the terminology of their choice, it is necessary for ABET volunteers and staff to have a consistent understanding of terminology. With that purpose in mind, the Commissions will use the following basic definitions: Program Educational Objectives-Program educational objectives are broad statements that describe what graduates are expected to attain within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…Roehrig et al () examined engineering curriculum implementation and found co‐teaching and collaboration to be productive for teachers’ STEM practice. Avery and Reeve () similarly found that with a supportive learning environment, engineering‐focused professional development had long‐term impact on classroom practice. Guzey, Tank, Wang, Roehrig, and Moore () analyzed a year‐long engineering‐integration program and found effective implementation of engineering practices in classroom contexts.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Roehrig et al () examined engineering curriculum implementation and found co‐teaching and collaboration to be productive for teachers’ STEM practice. Avery and Reeve () similarly found that with a supportive learning environment, engineering‐focused professional development had long‐term impact on classroom practice. Guzey, Tank, Wang, Roehrig, and Moore () analyzed a year‐long engineering‐integration program and found effective implementation of engineering practices in classroom contexts.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 98%
“…Although some literature has highlighted the importance of teachers to STEM education and called for teachers to cultivate their STEM thinking (e.g., National Research Council, ; Reeve, ), in general STEM teacher development has not yet been well defined or carefully studied. The research that does exist focuses primarily on professional development that builds STEM skills with practicing teachers (e.g., Avery & Reeve, ; Capobianco & Rupp, ; Roehrig, Moore, Wang, & Park, ). Very little research exists on how to most effectively prepare preservice teachers for STEM‐infused classrooms.…”
mentioning
confidence: 99%
“…Therefore, it is important for teachers and prospective teachers, especially at primary school level, to have professional development opportunities for STEM-oriented teaching (MacFarlane, 2016). Although STEM education approach is a current global reform, its future, especially in primary schools, is limited by teachers' capacity to be successful in this new paradigm (Avery & Reeve, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order for the US to stay globally competitive in terms of innovation and invention, the teaching of STEM has to become a priority in K-12 education today (Avery & Reeve, 2013). As the need for students to become stronger in STEM grows, so does the need for well-qualified teachers, who understand what is needed to develop relevant opportunities for those involved in STEM education.…”
Section: Introductionmentioning
confidence: 99%